The Annual of The NORTH DAKOTA Agricultural College 1914 - Poultry Show - North Dakota Agricultural College (Fargo, N.D.); Fargo (N.D.); (North Dakota State University Library, University Archives;, 1914)
THE 1914 AGASSIZ Poultry Show CHICKS (Haven't scratched yet) Katherine Ladd Hildur Sorenson Marion Cox Lena Honett CACKLING HENS (Hear 'em cackle) Edith Shelton Blanche McDonald Edna Steedsman Mabel Cox OLD HENS (Moulting) Warren Dodds Earnest Pile Grace Linder Tina McCarten Martha Munson? Lucy Glacier Eugenia Ruff Elizabeth Schriver Jennie Simmons Ethel Poole WADDLING DUCKS (Watch 'em waddle) Mildred Wheeler Gertrude Gibbens August Berg Olive Porter Dutch Schroeder Charles Hammond Albert Hammes Ruth Gardner Bert Haskins Reule Wije Gunhild Gilbertson Bertha Camp GEESE (Watch 'em stretch their necks) Ethel Poole Elsie Stark "Doc" Walter Clarence Williams Elmer Dynes Bob. Pearson Peggy Fosburg Dean Mendenhall OLD ROOSTERS Fred Householder Arthur Reuber M. N. Pope William Krechov T. Jackson E. D. Sylvester Leonard Wirtenberger Loyd Kelley PEACOCKS Mae Hooper Max Waldron Margaret Keene Arthur Ogaard David Sonquist Reg. Colley Wallace Manikowske Elsie Schuman Glen Livengood RARE BIRDS TURTLE DOVES Gross & Tarbell Taylor & Ogaard Gibbens & Waldron Viewbooks; 27 x 20 cm. Title taken from cover of book